IMPLEMENTASI MODEL PROTOTYPING INFRASTRUKTUR DAN JARINGAN PADA SMK KESATUAN CENGKARENG JAKARTA BARAT - RAYUNG WULAN; ABDUL MUFTI; BONDAN DWI HATMOKO (LPPM, 2016)
Prototyping is basically a technique in model development and network infrastructure. Prototyping is one method of software development and network technology as a supporting medium is necessary especially in education, especially among the middle school level ketas. Various ideas for the manufacturer or user of the system to determine how the network infrastructure that is suitable for education or other business world. In determining prototyping infrastructure can not be separated from the influence of technological development is growing rapidly, especially the rate of growth will need internet. The Internet is a network system formed from a variety of diverse components and infrastructure that mutual support between the components with one another. Internet has become part which can not be separated in various fields of education. All learning almost all connected by Internet connectivity. Prototyping their good infrastructure will make comfortable the students-students in the learning process and learning. No need to be expensive or Network Access Points (NPS) that are tricky to get the best results, but by building prototyping and network infrastructure that is appropriate to determine how and what steps are best to build it.Keywords: Model Prototyping, Infrastructure, Networking